2021
DOI: 10.31557/apjcp.2021.22.1.157
|View full text |Cite
|
Sign up to set email alerts
|

Role of miR153 and miR455-5p Expression in Oral Squamous Cell Carcinoma Isolated from Plasma

Abstract: Background: Despite the notable advances in modern surgery and radiotherapy,no significant increase in the five year survival rate of oral squamous cell carcinoma has been reported. Collecting evidence demonstrates that miR 153 and miR 455-5p play a key role in growth and progression of oral cancer. Early detection of OSCC is important for enhancing patient quality of life and clinical treatment.For this reason, biomarkers or tumour markers offer an opportunity to intervene and avoid development of oral cancer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…Although there is no direct evidence that hsa-miR-455-5p is associated with plasma exosomes of LSCC, however, studies have con rmed that it is highly expressed in laryngeal cancer, the expression level is more signi cant than that of adjacent noncancerous counterparts and benign laryngeal tissues [39], and is associated with prognosis [40]. Furthermore, hsa-miR-455-5p isolated from plasma has been proved to be an early diagnostic indicator of OSCC [41]. It may regulate the OSCC cell proliferation and promote the OSCC tumorigenesis through affecting PTPRS related pathway and transforming growth factor-β (TGF-β) pathway, these pathways were also common in HNSCC [42].…”
Section: Discussionmentioning
confidence: 99%
“…Although there is no direct evidence that hsa-miR-455-5p is associated with plasma exosomes of LSCC, however, studies have con rmed that it is highly expressed in laryngeal cancer, the expression level is more signi cant than that of adjacent noncancerous counterparts and benign laryngeal tissues [39], and is associated with prognosis [40]. Furthermore, hsa-miR-455-5p isolated from plasma has been proved to be an early diagnostic indicator of OSCC [41]. It may regulate the OSCC cell proliferation and promote the OSCC tumorigenesis through affecting PTPRS related pathway and transforming growth factor-β (TGF-β) pathway, these pathways were also common in HNSCC [42].…”
Section: Discussionmentioning
confidence: 99%
“…They have also suggested that miR-153 is an independent prognostic biomarker to predict the 3-year survival of PDAC patients (Bai et al, 2015). A recent study by Baber et al (2021) shows that miR-153 expression was low in the peripheral blood of oral squamous cell carcinoma patients than normal individuals and speculated that expression of miR-153 in the serum can function as a diagnostic biomarker (Baber et al, 2021). The meta-analysis data also shows the correlation between low mir-153 expression and poor overall survival of cancer patient and suggest miR-153 as an effective biomarker for various type of cancer (Huang et al, 2020).…”
Section: Mir-153 As a Biomarker In Cancermentioning
confidence: 98%
“…Baber S et al (2021) focused on miRNA-153 and miRNA-455-5p, which have been described to play a critical role in oral cancer development. Interestingly, the authors observed that the expression levels of miRNA-153 were decreased in the blood samples of OSCC patients than in healthy individuals (−1.97-fold), while the expression levels of miRNA-455-5p were increased (2.5-fold), suggesting that the detection of these liquid biopsy-based miRNAs could represent an adjuvant diagnostic tool [145]. Similarly, Nakamura K and colleagues (2021) evaluated the expression levels of cancer-associated miRNAs in the serum samples from OSCC patients.…”
Section: Mirnasmentioning
confidence: 99%